An l-cystine/l-cysteine impregnated nanofiltration membrane with the superior performance of an anchoring heavy metal in wastewater. Issue 6 (21st January 2020) - Zhang, Hong-Li; Cai, Huaqiang; Xia, Yu; Zhang, Pan; Xiong, Si-Wei; Gai, Jing-Gang
Abstract : Considerable efforts are being made to develop new materials and technologies for the efficient and fast removal of toxic ions in drinking water. Abstract : Considerable efforts are being made to develop new materials and technologies for the efficient and fast removal of toxic ions in drinking water. In this work, we developed a sulfur-complexed strategy to enhance the removal capability of heavy metal ions using the polyamide nanofiltration membrane by the covalent anchoring of l -cystine and l -cysteine. The sulfur-functionalized polyamide nanofiltration membrane exhibits superior complexation of heavy metal ions and can efficiently remove them from high-concentration wastewater. As a result, the sulfur-functionalized nanofiltration membrane not only showed excellent desalination performance but also achieved a record removal rate of heavy metal ions (99.99%), which can effectively reduce Hg(ii ) concentration from 10 ppm to an extremely low level of 0.18 ppb, well below the acceptable limits in drinking water (2 ppb). Moreover, the sulfur-functionalized nanofiltration membrane showed an exciting long-term stability and can be easily regenerated without significant loss of Hg(ii ) removal efficiency even after six cycles. Such outstanding performances were attributed to the synthetic effect of Hg–S coordinative interaction, electrostatic repulsion, and the sieving action of nanopores. These results highlight the tremendous potential of thiol/disulfide-functionalized NF active layer as an appealing platform for removing heavy metal ions from polluted water with high performance in environmental remediation.